2018
DOI: 10.17269/s41997-018-0035-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the risk factors and interventions for the prevention of playground injuries

Abstract: Equipment- and structure-based playgrounds should adhere to and maintain playground standards in order to reduce the risk of serious injury. Organizations responsible for installing and maintaining playgrounds should consider alternative play spaces that allow children to play outdoors, in a natural environment that supports healthy child development and promotes physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
(219 reference statements)
1
14
0
2
Order By: Relevance
“…There are relatively few studies that have evaluated specific playground factors associated with extremity fractures (Richmond et al 2018 ). In one case-control study regarding playground related-extremity fractures, investigators found that equipment height exceeding 1.5 m (4.92 ft) and fall height exceeding 1 m (3.28 ft) were risk factors for extremity fractures (Sherker and Ozanne-Smith, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are relatively few studies that have evaluated specific playground factors associated with extremity fractures (Richmond et al 2018 ). In one case-control study regarding playground related-extremity fractures, investigators found that equipment height exceeding 1.5 m (4.92 ft) and fall height exceeding 1 m (3.28 ft) were risk factors for extremity fractures (Sherker and Ozanne-Smith, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies on playground injuries, and more specifically, injuries associated with playground equipment, primarily are conducted with injury data from the United States and Canada. [10] The NEISS is used to collecting ED admission data associated with injuries due to products in the United States. [3–6] Likewise, Canada also collects hospital data associated with injuries through the Canadian Hospitals Injury Reporting and Prevention Program (CHIRPP).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of such epidemiological studies have been conducted using data limited to the United States and Canada. [10] Furthermore, the data solely analyzed patients particularly injured by playground equipment. [28] As such, the aforementioned studies did not include the myriad types of injuries that can occur within the playground, apart from the use of playground equipment.…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by the increase in adventurous behaviours that occur during middle childhood despite incomplete development of neuromuscular coordination 15 . The potential for risky behaviour and equipment misuse are also important etiological considerations for playground injuries across all age groups 1,16 . For these reasons, in addition to safety standard compliance, targeted education to care‐givers and school staff regarding conscious supervision and appropriate playground behaviours remains imperative.…”
Section: Discussionmentioning
confidence: 99%